Efficacy and safety of empagliflozin, a sodium glucose cotransporter 2 (SGLT2) inhibitor, as add‐on to metformin in type 2 diabetes with mild hyperglycaemia. Issue 12 (22nd August 2013) - Rosenstock, J.; Seman, L. J.; Jelaska, A.; Hantel, S.; Pinnetti, S.; Hach, T.; Woerle, H. J.
Abstract : Aims: To evaluate the effects of the sodium glucose cotransporter 2 (SGLT2) inhibitor empagliflozin added to metformin for 12 weeks in patients with type 2 diabetes. Methods: This dose‐ranging, double‐blind, placebo‐controlled trial randomized 495 participants with type 2 diabetes inadequately controlled on metformin [haemoglobin A1c (HbA1c) >7 to ≤10%] to receive 1, 5, 10, 25, or 50 mg empagliflozin once daily (QD), or placebo, or open‐label sitagliptin (100 mg QD), added to metformin for 12 weeks. The primary endpoint was change in HbA1c from baseline to week 12 (empagliflozin groups versus placebo). Results: Reductions in HbA1c of −0.09 to −0.56% were observed with empagliflozin after 12 weeks, versus an increase of 0.15% with placebo (baseline: 7.8–8.1%). Compared with placebo, empagliflozin doses from 5 to 50 mg resulted in reductions in fasting plasma glucose (−2 to −28 mg/dl vs. 5 mg/dl with placebo; p < 0.0001) and body weight (−2.3 to −2.9 kg vs. −1.2 kg; p < 0.01). Frequency of adverse events was generally similar with empagliflozin (29.6–48.6%), placebo (36.6%) and sitagliptin (35.2%). Hypoglycaemia rates were very low and balanced among groups. Most frequent adverse events with empagliflozin were urinary tract infections (4.0% vs. 2.8% with placebo) and pollakiuria (2.5% vs. 1.4% with placebo). Genital infections were reported only with empagliflozin (4.0%). Conclusions: Once daily empagliflozin as add‐on therapy to metformin was well tolerated except for increased genital infections and resulted in reductions in HbA1c, fasting plasma glucose and body weight in patients with type 2 diabetes inadequately controlled on metformin monotherapy.